The Influence of Online and Offline Strategic Marketing Communication to Purchase Intention of Singapore Airlines - Pratiwi Mulyantina (CoverAge: Journal of Strategic Communication, 2019)
The purpose of this thesis is to find out which of Singapore Airline to promote Premium Economy Class, both online and offline marketing communication channels, has greater impact to increase its Product Awareness and come out with Marketing Strategies purchase decision.This study uses quantitative method by finding out the influence of online and offline Strategic Marketing Communication by Singapore Airlines Premium Economy Class in Purchase Intention followed by post-positivist paradigm and mix method. As the result, the researcher uses 100 correspondences who are Indonesian passengers living in Jakarta and usually travel on Singapore Airlines and registered as Singapore Airlines members. The research result shows that (1) Brand Awareness in online marketing strategies has a greater influence on Purchase Intention at 41.2% while Brand Awareness in the offline marketing strategies has an influence of 33%, (2) brand knowledge on online marketing strategies has a greater influence on Purchase Intention at 48.1% while Brand knowledge in offline marketing strategies has an influence of 15.7%, (3) Brand likeness in online marketing strategies has a greater influence on Purchase Intention at 47.3% while Brand likeness in offline marketing strategies has an influence of 20.7%, (4) Brand preference on online marketing strategies has a greater influence on Purchase Intention at 52.1% while Brand preference on offline marketing strategies has an influence of 24.9%, (5) brand conviction on online marketing strategies has a greater influence on Purchase Intention at 54% while brand conviction in offline marketing strategies has an influence of 26.6%